COSMOLOGY, COSMOMICROPHYSICS AND GRAVITATION - Alexandrov, A. N.; Zhdanov, V. I.; Koval, S. M. (Одеські астрономічні публікації, 2013)
We derive approximate formulas for the coordinates and magnification of critical images of a point source in a vicinity of a cusp caustic arising in the gravitational lens mapping. In the lowest (zero-order) approximation, these formulas were obtained in the classical work by Schneider&Weiss (1992) and then studied by a number of authors; first-order corrections in powers of the proximity parameter were treated by Congdon, Keeton and Nordgren. We have shown that the first-order corrections are solely due to the asymmetry of the cusp. We found expressions for the second-order corrections in the case of general lens potential and for an arbitrary position of the source near a symmetric cusp. Applications to a lensing galaxy model represented by a singular isothermal sphere with an external shear y are studied and the role of the second-order corrections is demonstrated.